PENGARUH SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MINUMAN MEREK AQUA BERKAITAN DENGAN PENERAPAN PROGRAM CSR (CORPORATE SOCIAL RESPONSIBILITY) - Sarwoko, Endi; Churiyah, Madziatul (Jurnal Ekonomi Modernisasi, 2007)
This research was purposed to explain the influence of consumers’ attitude toward their decision to purchase related to the application of CSR program. Consumers’ attitude toward the application of CSR program done by Aqua. Has been observed over cognitive and affective component. Analysis technique their used was in this research multiple regression technique analysis. The result of this research concluded that consumer had a positive attitude toward the application of Aqua CSR program. From this research, it could be proved that consumers’ attitude related to the application of CSR program significant effect toward consumers’ purchase decision